2016
DOI: 10.1590/1518-8345.1276.2840
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and coping with the altered body image in digestive stoma patients

Abstract: Objective:to describe the coping of stoma patients with the news about the ostomy, as well as to analyze the meaning and the experience of their new bodily reality. Method:qualitative phenomenological study undertaken through semistructured interviews with 21 stoma patients. The analysis was based on the constant comparison of the data, the progressive incorporation of subjects and triangulation among researchers and stomal therapy nurses. The software Atlas.ti was used. Results:two main categories emerge: "Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 19 publications
4
25
0
3
Order By: Relevance
“…"Regarding the diagnosis of Disturbed body image (00118)," in addition to being more likely in follow-up care, the multivariate analysis showed that the likelihood of this diagnosis was 2.59 times higher in women than in men. This aspect has been contrasted with the literature consulted, which supports that body modification due to the ostomy requires greater adaptation to the new condition by women (De-Sousa et al, 2014) and suggests the need to develop different strategies by sex, highlighting the role of information (Hueso-Montoro et al, 2016) and psychological support (Di-Pretoro, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…"Regarding the diagnosis of Disturbed body image (00118)," in addition to being more likely in follow-up care, the multivariate analysis showed that the likelihood of this diagnosis was 2.59 times higher in women than in men. This aspect has been contrasted with the literature consulted, which supports that body modification due to the ostomy requires greater adaptation to the new condition by women (De-Sousa et al, 2014) and suggests the need to develop different strategies by sex, highlighting the role of information (Hueso-Montoro et al, 2016) and psychological support (Di-Pretoro, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…In spite of the national preventative measures and programs, the trend of colorectal and rectal cancer together became the third most common cause of death in 2017, with an incidence of 16% in males and 13% in females [3]. Colorectal cancer is the second most common cause of death in men and women in Europe, with 446,000 newly diagnosed cases each year [4]. According to unofficial data, since there is no register or database of persons with ostomy in the Republic of Croatia, it is estimated that there are about 7500 persons suffering from this condition, which is about 0.2% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Professionals and the family have the role of educating for self-care, attending to individual needs, respecting the limitations and arousing the interest of taking care of oneself to obtain a better quality of life. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Individuals with intestinal ostomy are considered to be threatened in performing their daily activities, either because they present feelings of insecurity, limitations or physical incapacity, establishing in their lives significant daily changes. With such changes, illness goes beyond physical illness and diffuses into all dimensions of being, causing discontinuities and empty spaces, which imply reflection of values, priorities and life projects.…”
Section: /13mentioning
confidence: 99%
“…For effective rehabilitation, the subjectivity and the sociocultural aspects that integrate the experiences of the people with the ostomy should be considered. [18][19][20][21] The inability of fecal control associated with the need to use fecal collection devices requires a new way of living. 20 Amongst the changes resulting from surgery for the manufacture of the ostomy, in addition to changes in diet, the interviewees mentioned daily changes that require adaptation to be experienced, among them: domestic tasks, sexuality, sports practice, work, and activities of leisure.…”
Section: /13mentioning
confidence: 99%
See 1 more Smart Citation